Cyclic hematopoiesis. Effects of endotoxin on colony-forming cells and colony-stimulating activity in grey collie dogs. - Hammond, W P (1979)
Cyclic changes in blood neutrophil counts of grey collie dogs with cyclic hematopoiesis can be eliminated by daily endotoxin injections. Studies were performed to determine the mechanism whereby endotoxin alters this disease. Bone marrow granulocyte-macrophage progenitor cells (colony-forming cells [CFUc]) showed cyclic variation in the untreated grey collie, which was eliminated by chronic endotoxin treatment (Salmonella typhosa lipopolysaccharide W, 5 microgram/kg per day). Similar cyclic variation in blood CFUc was eliminated by this treatment. Tritiated thymidine suicide of the marrow colony-forming cells failed to show cyclic changes to explain the marked swing in CFUc numbers in untreated grey collies. The thymidine suicide rates were not significantly changed by chronic endotoxin treatment. Similarly, serum colony-stimulating activity did not show cyclic variation with the cyclic neutrophil counts in untreated grey collies and was not altered by chronic endotoxin treatment. We suggest that endotoxin eliminates neutrophil cycling in cyclic hematopoiesis by a direct effect on the flux of pluripotent stem cells into the committed stem cell compartment and that this occurs independent of changes in serum colony-stimulating activity.